Kewenangan Satuan Polisi Pamong Praja Dalam Pengamanan Aset Daerah Pemerintah Provinsi Sulawesi Selatan - Firman Anugrah; Syamsul Bachri; Juajir Sumardi (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to identify and explain the implementation of the Authority of the Civil Service Police Unit in Securing Regional Assets of the South Sulawesi Provincial Government. To find out and explain the settlement of violations committed by the Civil Service Police Unit in Safeguarding Regional Assets for the South Sulawesi Provincial Government. This research uses normative-empirical research. The types and sources of law used in this research are document data and secondary data. Methods of collecting data through interviews and documentation, all of the data were analyzed qualitatively and presented in descriptive form. The results of the study show that the authority of the Civil Service Police Unit in securing regional assets of the South Sulawesi Provincial Government is the authority of the delegation, the authority that transfers responsibility to those who are given the authority in this case the regional secretary based on the BKAD letter which is dispositioned to Satpol PP, the delegation's authority is created because of their attribution authority, authority sourced from Law No. 23 of 2014, PP No. 16 of 2018 and Regional Regulation No. 3 of 2017. and Settlement of violations of the Civil Service Police Unit in securing regional assets of the South Sulawesi Provincial Government is carried out by PPNS Satpol PP in coordination and supervision of investigators the police with the process of investigation, examination, summons and solution.